2020
DOI: 10.1007/s13205-020-2058-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of eukaryotic translation initiation factors and the temperature-dependent nature of Turnip mosaic virus epidemics in allopolyploid Brassica juncea

Abstract: Eukaryotic translation initiation factors (eIFs) are essential protein complexes involved in the translation of mRNA into proteins. These initiation factors are generally used as targets in the control of plant RNA virus infections. In the present study, we identified a total 190 eIFs, clustered phylogenetically into 40 distinct subfamilies in the allopolyploid Brassica juncea. Extensive evolutionary duplications of the eIFs in B. juncea suggest their increased genetic diversity and wide adaptability. The indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…A similar conclusion was reached from an analysis of Arabidopsis plants from a transposon insertion library in which an eIF(iso)4E mutant line was identified and shown to be resistant to TuMV and the potyvirus lettuce mosaic virus (Duprat et al, 2002). These studies led to testing genes encoding eIF4E, eIF(iso)4E, as well as other eukaryotic translation factors, of other plant species, as candidate recessive resistance genes (reviewed by Shopan et al, 2020aShopan et al, , 2020b. Another study also showed that an Arabidopsis mutant line with a mutation in eIF(iso)4E was unable to support infection by TuMV, but supported infection by the potyvirus clover yellow vein virus, while an Arabidopsis mutant line with a mutation in eIF4E was able to support infection by TuMV, but not clover yellow vein virus (Sato et al, 2005).…”
Section: Resistance Genes In Arabidopsismentioning
confidence: 64%
See 1 more Smart Citation
“…A similar conclusion was reached from an analysis of Arabidopsis plants from a transposon insertion library in which an eIF(iso)4E mutant line was identified and shown to be resistant to TuMV and the potyvirus lettuce mosaic virus (Duprat et al, 2002). These studies led to testing genes encoding eIF4E, eIF(iso)4E, as well as other eukaryotic translation factors, of other plant species, as candidate recessive resistance genes (reviewed by Shopan et al, 2020aShopan et al, , 2020b. Another study also showed that an Arabidopsis mutant line with a mutation in eIF(iso)4E was unable to support infection by TuMV, but supported infection by the potyvirus clover yellow vein virus, while an Arabidopsis mutant line with a mutation in eIF4E was able to support infection by TuMV, but not clover yellow vein virus (Sato et al, 2005).…”
Section: Resistance Genes In Arabidopsismentioning
confidence: 64%
“…Arabidopsis was shown to contain several genes for resistance to TuMV, some of which have been cloned, while others represent possible candidate genes that could be explored for mapping and evaluation in syntenic crop species, such as brassicas or radish. The identification of genes expressing translation factors [eIF(iso)4E and others] in Arabidopsis, which confer recessive resistance to TuMV and other potyviruses has led to such genes being sought out as candidate resistance genes in various crops (reviewed by Shopan et al, 2020aShopan et al, , 2020b. In addition, various laboratories have developed novel forms of resistance against TuMV, by, intragenic (genes from related and sexually compatible species), cisgenic (genes from related but sexually incompatible species) or transgenic means; the last using expression of either TuMV sequences to induce RNA silencing, or other genes from various sources, usually in a model system, but also in brassica.…”
Section: Discussionmentioning
confidence: 99%
“…The only BjueIFs suggested in the chromosome A06 QTL associated with TWBJ20 were BjuA022587 and BjuA023685 ; these are both proposed by Shopan et al (2020) to be homologs of eIF2ß . Of these two putative eIF2ß genes, BjuA023685 was also contained within the A06 QTL associated with TWBJ14 resistance.…”
Section: Discussionmentioning
confidence: 98%
“…As with retr01 -based resistance in B. rapa , it is possible that eIF4E/eIF(iso)4E allelic variants (which TuMV cannot use) could be candidates for retr04 , retr05 , and retr06 . Shopan et al (2020) used sequence data of 95 established eukaryotic translation initiation factors ( eIFs ) from Arabidopsis thaliana to identify homologs across various Brassica species, including 190 putative B. juncea eIFs ( BjueIFs ). Using the positions of these BjueIFs on the B. juncea cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation